Pengaruh Seleksi dan Pelatihan terhadap Prestasi Kerja Karyawan pada PT. Adimulia Palmo Lestari di Desa Peninjauan - Ratna Ratna; Rts Hartha Delima (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this study is to explain the effect of selection and training on employee performance at PT. Adimulia Palmo Lestari in the village of Peninjauan. The analytical method used is quantitative using multiple linear regression analysis tools. Testing the significance of the influence of selection variables (X1) and training (X2) as independent variables and employee performance (Y) as the dependent variable carried out t test and F test. The results of testing the hypothesis on the effect of selection variables on employee performance that the t count is 3.560> from the t table 1.667 and the significance number is (sig) 0.001 <from the level of significance (α) 0.05 (5%), thus it can be known that selection has an influence on employee performance. The results of testing the hypothesis of the effect of training variables on employee performance that the t count is 2.089> from the t table 1.667 and the significance number is (sig) 0.004 <from the level of significance (α) 0.05 (5%), thus it can be known that training has an influence on employee performance. The results of testing the hypothesis of the selection and training variables on employee performance shows that the F value obtained F count 15.956 with a significance level of (0.000 <0.05), the value of F table of 3.11 means that F count (15.995) > F table (3.11) thus Ho is rejected and Ha is accepted, meaning that selection (X1) and training (X2) have a positive effect simultaneously or together on the work performance of employees of PT. Adimulia Palmo Lestari in the village of Peninjauan. Adjusted R square generated is 0.265. So it can be concluded that the percentage of the effect of selection and training on employee performance at PT. Adimulia Palmo Lestari amounted to 26.5% and the remaining 73.5% was influenced by other variables not examined in this study.